Larangan Aktivitas Jemaat Ahmadiyah Indonesia (JAI) di Jawa Timur dalam Perspektif External Protection dan Internal Restriction Will Kymlicka - Alawiyah, Aimmatul (Religió: Jurnal Studi Agama-agama, 2016)
In order to protect Ahmadiyah in East Java, the executive body of East Java Province has issued a Degree No. 188/94/KPTS/013/2011 regarding the prohibition of the Ahmadi’s activity in east java. However, it becomes controversial. On one hand, it is considered protecting minority’s right, but on the other hand, it also weakens the position of Ahmadiyah toward majority’s group outside Ahmadiyah. One implication of the degree is the loss of the primer rights of the group in worshiping their belief in accordance with their faith. Combining Kymlicka’s external protection and internal restriction, this article attempts to analyze the implication from the government degree. The basic assumption of this article is that the country is incapable to protect the existence of minority group, Ahmadiyah. The finding shows that the Government of East Java cannot protect the principle rights of Ahmadiyah, especially the right to worship based on their religious belief. As a response to this restriction, Ahmadiyah has applied an internal restriction towards their members that protect themselves from the majority. However, this restriction does not have a penalty so it is considered protecting individual rights of Ahmadiyah group.